1997
DOI: 10.1002/eji.1830270938
|View full text |Cite
|
Sign up to set email alerts
|

Priming of cytotoxic T lymphocytes by five heat‐aggregated antigens in vivo: Conditions, efficiency, and relation to antibody responses

Abstract: Mice were immunized i.p. with soluble or heat-denatured protein antigens [ovalbumin, beta-galactosidase, or recombinant E7 protein of human papilloma virus type 16 (HBV)]. Heat-denatured (100 degrees C) preparations of these proteins were able to induce cytotoxic T lymphocytes (CTL) that recognize cells expressing the respective genes, whereas native protein was either inefficient or required up to 30-fold higher doses. If the heat-treated proteins were separated into aggregated and soluble fractions by ultrac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
53
0

Year Published

1998
1998
2010
2010

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(54 citation statements)
references
References 60 publications
1
53
0
Order By: Relevance
“…Our results suggest that multiepitope polypeptides can be potent immunogens due to their capacity to aggregate and form particulates. Previous studies by other groups have provided similar evidence supporting this hypothesis (17)(18)(19)(20)(21). Finally, our results suggest that multiepitope polypeptides might offer significant advantages in terms of priming for memory CD8 ϩ IFN-␥ responses, compared with DNA vaccines.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Our results suggest that multiepitope polypeptides can be potent immunogens due to their capacity to aggregate and form particulates. Previous studies by other groups have provided similar evidence supporting this hypothesis (17)(18)(19)(20)(21). Finally, our results suggest that multiepitope polypeptides might offer significant advantages in terms of priming for memory CD8 ϩ IFN-␥ responses, compared with DNA vaccines.…”
Section: Discussionsupporting
confidence: 89%
“…In most cases, exogenous Ags that effectively induce class I-restricted responses are particulate, and may access a specialized uptake mechanism by professional APCs (17)(18)(19)(20)(21). Class I-restricted presentation can also occur via binding to surface MHC by short peptides generated or present extracellularly (22,23).…”
mentioning
confidence: 99%
“…By this reason, rather than serving as target cells, tumor vaccines must be processed and presented to MHC I molecules by professional APCs to induced CTL responses. Although the experimental conditions were different, our results along with Speidel et al (1997) clearly indicated that tumor cell extracts can be processed and presented to not only CD4 + T cells but also CD8 + T cells through cross priming as were shown by target cell-specific CTL responses. For the cross priming of CD8 + T cells by the extracellular antigens, phagocytosed antigens need to be processed either in the cytosol or the antigens processed in the lysosomal compartment need to be transported to endoplasmic reticulum, where cross presentation to the MHC I occurs (Shen and Rock, 2006).…”
Section: Discussionmentioning
confidence: 53%
“…Thus, it remains possible that the denatured form of self-molecules, which were introduced during the preparation of the HK vaccine, might be detected by TLRs. Speidel et al (1997) also showed that heat-denatured protein antigens were able to enhance antigenspecific CTL responses. Interestingly in their paper, stronger minor antigen H-specific CTL response was induced when the recipients were immunized with fresh spleen cells compared to heat-killed spleen cell-immunization.…”
Section: Discussionmentioning
confidence: 94%
“…30 The higher proliferative response that we obtained using Apo-DC may be attributed to the fact that particulate antigens prime T-cell more effectively. 31 Furthermore, residual nonhybridised B-CLL cells may serve to anergise T-cells. 32 All these parameters may affect the proliferation response when using DC fusion hybrids to stimulate autologous antileukaemic T-cells.…”
Section: Figurementioning
confidence: 99%